Analysis of quasi-square-wave operation of DAB DC–DC converter. Issue 1 (2nd January 2016) - Naayagi, R.T.; Forsyth, A.J.; Shuttleworth, R.
Abstract : This work makes a novel contribution to the analysis of quasi-square-wave operation of dual-active bridge (DAB) converter by deriving equations for root mean square (RMS) and average device currents and RMS and peak inductor/transformer currents – these equations are useful in predicting device and passive component losses. Quasi-square-wave operation of the DAB converter is verified through Saber simulations and experimentation, validating the mathematical analysis. It is observed that quasi-square-wave mode improves average power transfer and the converter efficiency besides enhancing its soft-switching region without introducing additional passive components. The effect of quasi-square-wave on RMS and peak currents of devices and transformer/inductor is also discussed.